Narrow-diameter implant in prosthodontics treatment - Delicia Clarance Song; Lia Kartika Wulansari (Indonesia Prosthodontic Association, 2023)
Insufficient bone volume and narrow mesiodistal space often compromise Standard Diameter Implant (SDI) treat-ment planning. In order to achieve successful results, these compromises may incorporate prior treatment such as guided bone regeneration (GBR), block bone grafting, or distraction osteogenesis that requires extra time and cost and could result in unpredictable complications. A narrow diameter implant (NDI) is smaller than a standard diame-ter implant with a diameter less than 3.5 mm. This scoping review was performed to assess the use of NDI in pros-thodontic care. It is concluded that NDI reasonably resembles SDI clinical success rate in terms of periodontal health, marginal bone remodeling, restoration, and patient satisfaction. The NDI offers similar survival rate to SDI, with pro-mising long-term esthetic outcomes and can be used as the primary treatment alternative in restoring single tooth or splinted crowns in the anterior and posterior region, especially with narrow mesiodistal space.